ERRATUM: Néel State in the Fermionized Spin \(\frac{1}{2}\) Heisenberg Antiferromagnet on Hypercubic and Triangular Lattices [Pham Thi Thanh Nga and Nguyen Toan Thang, \(Comm. Phys. 22\) (1) (2012) 33] - Nga, Pham Thi Thanh; Thang, Nguyen Toan (Communications in Physics, 2013)
ERRATUM: Néel State in the Fermionized Spin \(\frac{1}{2}\) Heisenberg Antiferromagnet on Hypercubic and Triangular Lattices [Pham Thi Thanh Nga and Nguyen Toan Thang, \(Comm. Phys. 22\) (1) (2012) 33]